The Defending of State as a Nation-State Awareness : A Non Military Perspective - Hermawanto, Ariesani; Muryantini, Sri (RSF Conference Series: Business, Management and Social Sciences, 2021)
The defending of state is basically a value that exists in every state society and nations around the world; who want to maintain their existence, integrity and sovereignty, as well as their national integration. The issues raised are about what problems are faced by the nation-state in the context of maintaining its existence, the form of defending the state in general from the perspective of sovereignty and national integration. The method that is used here by observing various literatures related to the subject matter raised, whether in the form of books, papers or writings that are helpful so that they can be used as guidelines in the research process. This research focuses on theoretical studies and analysis as well as implementation of defending of state from a non-military point of view, which is based on a sense of belonging based on the awareness of maintaining the existence of the state and the nation (nation-states awareness). The result of this research show that defending the state is based on strong nation-state awareness, so the people in a state can produce a high esteem for their country and are willing to defend it from various threats.